Challenge of edible oils: Can Brassicas deliver - Arvind Kumar (Journal of Oilseed Brassica, 2026)
Agriculture University, Ludhiana, Dr. P.R. Verma,Agriculture and Agri-Food Canada, ResearchStation, Saskatoon, Canada, Dr. S.J. Kolte, ExProfessor, GB Pant University of Agriculture andTechnology, Pantnagar, Professor Martin Barbetti,University of Western Australia, Deans, Directorsof State Agricultural Universities (SAUs),Directors of ICAR Institutes, representatives fromprivate sector, distinguished participants, mediapersonnel, ladies and gentlemen.